The economic impact of mining on Jaguas of Ibirico, Cesar (2014)
The emergence of mining in the township of Ibirico Jaguas, Department of Cesar, has been replacing the traditional shape fieldwork such as agriculture, livestock etc., as well as the force that has made the exploitation. Coal walking strengthening of national development by promoting large-scale investment, this being one of the important pillars that leave its mark on the growth of the economy. The way extraction how economic compensation that leaves mineral extraction are distributed to the town, which in this case would be the distribution of royalties, and how ambitious the project is Sleep by area representing dimension is why the government has directed all its efforts to coalmining contributing largely to the GDP.